Assessment of the Safety of Wild Strains of Lactobacillus as Probiotics Orogastrically Administered to Rats (Biological Sciences - PJSIR, 2005)
The safety of four  wild strains of Lactobacillus, isolated from fresh cow milk and faeces of albino rat (Rattus norvegicus)  was  studied. Some biochemical parameters of the serum in the orogastrically-dosed rats were used as the index. A reduction in the levels of  serum cholesterol and of serum aminotranferases in the rats orogastrically-dosed with Lactobacillus isolates, as compared with  the control  group was noted. There was no significant difference (P > 0.05) in the alkaline phosphatase levels of the control and the orogastrically-dosed rat  groups. Serum globulin and bilirubin levels showed a significant difference (P 0.05) from other treatments except in the rats dosed with the Lactabacillus casei strain isolated from cow milk. The rats dosed with Lactobacillus displayed beneficial effects as probiotics in terms of reduced serum cholesterol and liver function improvement in terms of reduction in the serum aminotransferase levels.